Incidence of HIV in Sub-Saharan Africa, 2000–2015: The Interplay Between Social Determinants and Behavioral Risk Factors. - Jahagirdar, Deepa; Walters, Magdalene; Vongpradith, Avina; Dai, Xiaochen; Novotney, Amanda; Kyu, Hmwe H.; Wang, Haidong (AIDS & Behavior)
HIV incidence in sub-Saharan Africa declined substantially between 2000 and 2015. In this analysis, we consider the relative associations of nine structural and individual determinants with this decline. A linear mixed effects model of logged HIV incidence rates versus determinants was used. The data were from mathematical modelling as part of the 2019 Global Burden of Disease Study in 43 sub-Saharan African countries. We used forwards selection to determine a single final model of HIV incidence rate. The association of economic variables and HIV knowledge with incidence was found to be driven by education, while ART coverage had the largest impact on other determinants' coefficients. In the final model, education years per capita contributed the most to explaining variation in HIV incidence rates; a 1-year increase in mean education years was associated with a 0.39 (− 0.56; − 0.2, t = − 4.48 p < 0.01) % decline in incidence rate while a unit increase in ART coverage was associated with a 0.81 (− 1.34; − 0.28, t = − 3.01, p < 0.01) % decline in incidence rate.